Hereditary Xerocytosis due to Mutations in PIEZO1 Gene Associated with Heterozygous Pyruvate Kinase Deficiency and Beta-Thalassemia Trait in Two Unrelated Families - Elisa Fermo; Cristina Vercellati; Anna Paola Marcello; Anna Zaninoni; Richard van Wijk; Nadia Mirra; Cristina Curcio; Agostino Cortelezzi; Alberto Zanella; Wilma Barcellini; Paola Bianchi (Case Reports in Hematology)
Hereditary xerocytosis (HX) is a rare disorder caused by defects of RBC permeability, associated with haemolytic anaemia of variable degree and iron overload. It is sometimes misdiagnosed as hereditary spherocytosis or other congenital haemolytic anaemia. Splenectomy is contraindicated due to increased risk of thromboembolic complications. We report the clinical, haematological, and molecular characteristics of four patients from two unrelated Italian families affected by HX, associated with beta-thalassemia trait and heterozygous pyruvate kinase deficiency, respectively. Two patients had been splenectomised and displayed thrombotic episodes. All patients had iron overload in the absence of transfusion, two of them requiring iron chelation. The diagnosis of HX was confirmed by LoRRca Osmoscan analysis showing a left-shifted curve. PIEZO1 gene sequencing revealed the presence of mutation p.E2496ELE, showing that this is one of the most frequent mutations in this disease. The concomitant defects did not aggravate the clinical phenotype; however, in one patient, the initial diagnosis of pyruvate kinase deficiency delayed the correct diagnosis of HX for many years and resulted in splenectomy followed by thrombotic complications. The study underlines the importance of a precise diagnosis in HX, particularly in view of splenectomy, and the need of a molecular confirmation of suspected RBC enzymopathy.